CONVERSION OF LINOLEIC ACID TO DIFFERENT FATTY ACID METABOLITES BY LACTOBACILLUS PLANTARUM 13-3 AND IN SILICO CHARACTERIZATION OF THE PROMINENT REACTIONS - Aziz, Tariq; Sarwar, Abid; Fahim, Muhammad; Al Dalali, Sam; Ud Din, Zia; Ud Din, Jalal; Pacheco Fill, Taicia; Zhennai, Yang (Journal of the Chilean Chemical Society, 2020)
Lactobacillus plantarum strains have been extensively used in food processing and preservation. L. plantarum also has the potential to convert polyunsaturated fatty acids, e.g. linoleic acid (LA) into bioactive and less toxic fatty acid metabolites. The objective of this study was to assess the capability of probiotic L. plantarum 13-3 to convert Linoleic Acid (LA) to different fatty acid metabolites in the medium supplemented with differential concentrations of LA, and the relevant reactions were characterized by in silico calculation. L. plantarum 13-3 was grown in MRS medium containing LA from 1% to 10%, and the fatty acid metabolites formed in the medium were identified and quantitated by GC-MS and in silico studies were done to confirm the enzymatic reactions involved in its conversion. The results showed that L. plantarum 13-3 could convert LA at different concentrations to 5 different fatty acid metabolites i.e, (Z)-Ethyl heptadec-9-enoate, 9,12-Octadecadienoic acid (Z, Z), methyl ester, Octadec-9-enoic acid, cis-11,14-Eicosadienoic acid, methyl ester and (Z)-18-Octadec-9-enolide. Among these metabolites, the formation of an long chain fatty acid Octadec-9-enoic Acid, also known as 18:1, N-9 or Delta(9)-Octadecenoic acid, is classified as a member of the Long-chain fatty acids in media supplemented with 4% to 10% LA, is being reported for the first time. Putative candidate enzymes involved in biotransformation of LA into fatty acid metabolites were identified in whole genome of L. plantarum 13-3, sequenced previously. In silico studies confirmed that several enzymes including the linoleate isomerase, acetoacetate decarboxylase and oxidoreductase may be involved in biotransformation of LA into fatty acid metabolites. These enzymes could effectively bind the LA molecule mainly by forming hydrogen bonding between the acidic groups of LA and the proline residues at the active sites of the enzymes validating the putative reacting partners.